THE EFFECT OF COMPETENCE AND CONFIDENCE ON THE PERFORMANCE OF ACTIVITIES TECHNICAL IMPLEMENTING OFFICERS (PPTK) WITH MOTIVATION AS INTERVENING VARIABLES IN GOVERNMENT BINTAN REGENCY - Rachmad Chartady; Sri Kurnia; Charly Marlinda; Salihi Salihi; Andres Putranta Sitepu (International Journal of Social Science, 2023)
This study aims to determine the Influence of Employee Competence and Confidence Against the Performance of Officials of Technical Activities (PPTK) With Motivation Employees as Intervening Variables partially or simultaneously in the Government of Bintan Regency. Population in this research is All ASN which become PPTK amounted to 329 employees. In this study the authors narrowed the population of the total number of PPTK to 181 ASN.The results of this study can be concluded Competence directly affects positively and significantly to Performance of PPTK. Self Confidence and Motivation have a direct and positive direct effect on PPTK Performance. Competence and Self Confidence have a direct and positive direct effect on Motivation. Competence has a significant effect on PPTK Performance not through Motivation. Or in other words Motivation is not an intervening variable between Competence with PPTK Performance. This shows that the actual influence between Competence on PPTK Performance is direct influence. Confidence has a significant effect on PPTK Performance not through Motivation. Or in other words Motivation is not an intervening variable between Confidence with Performance PPTK. This shows that the actual influence between confidence on the performance of PPTK is a direct influence.